2006 IEEE/ACM International Symposium on Mixed and Augmented Reality 2006
DOI: 10.1109/ismar.2006.297790
|View full text |Cite
|
Sign up to set email alerts
|

User evaluations on form factors of tangible magic lenses

Abstract: Magic Lens is a small inset window embedded in a large context display, which provides an alternative view to the region of interest selected from the context view. This metaphor is used for 3D visualization in our Augmented Virtual Environment infrastructure, SCAPE (Stereoscopic Collaboration in Augmented and Projective Environments), which is composed of an immersive room display for a high level of detail, life-size virtual world and a workbench display for simplified god-like view to the world. A tangible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Oh and Hua tested various aspect ratios and sizes of spatially aware peepholes [18]. They concluded that the aspect ratio of a display plays a more important role for smaller screens than for larger ones and that screen sizes are more dominant in impacting the user performance.…”
Section: Related Workmentioning
confidence: 99%
“…Oh and Hua tested various aspect ratios and sizes of spatially aware peepholes [18]. They concluded that the aspect ratio of a display plays a more important role for smaller screens than for larger ones and that screen sizes are more dominant in impacting the user performance.…”
Section: Related Workmentioning
confidence: 99%
“…Researchers have looked into these questions via simulation [21,17] and via real AR magic lenses [25,26]. Oh et al [21] looked at the effects of magic lens display size and screen aspect ratio on a search and a path following task. Their results indicated that, in general, a larger magic lens was better for searching while a smaller magic lens was better for path following.…”
Section: Related Workmentioning
confidence: 99%
“…Even though the designed task is artificial, this interaction pattern is analogous to navigation and route-planning on augmented paper maps. Additionally, as Oh and Hua used a similar methodology, it was deemed appropriate [21].…”
Section: Experimental Approachmentioning
confidence: 99%